“I cheated and got away with it” : the influence of descriptive norms of trickery and the cultural context on dishonest behavior and corruption intentions - Farias, Jéssica Esther Machado (2022)
Tese (doutorado) — Universidade de Brasília, Instituto de Psicologia, Programa de Pós-graduação em Psicologia Social, do Trabalho e das Organizações, 2022.